Diplomatic Protection of the “Bipadrids” - Persons with Dual Citizenship - Amina A. Nagiyeva (Московский журнал международного права, 2015)
The article analyzes the issue focusing on two subjects: the legal status of persons with the nationality of two or more States (dual nationals) and the institution of diplomatic protection under existing customary and conventional international law and applicable national law. Particular attention is paid to the issue of diplomatic protection for dual nationals at the level of bilateral agreements. In the analysis of the institution of diplomatic protection for dual nationals considered the practice of litigation, which has a huge importance, as, tools for the determination of the applicable rules of international customary law.